Barriers and facilitators of purchasing from short food supply chains in europe: insights from a stakeholder perspective - Verena Hüttl-Maack; Betty Chang; Susanne Braun; Frank Janssen; Jasper Kuitems; Marieke Lameris; Elena Santa Cruz; Begoña Alfaro; Eugenia Petropoulou; Dennis Gawlik; Camille Aouinait; Ágnes Szegedyné Fricz; et al. (International Journal of Food Studies)
Thirty-two expert stakeholder (e.g., consumer advice center, state parliament at regional level, European Network for Rural Development, university and research center, chamber of tourism, rural development association, and social cooperative enterprise) interviews were conducted to examine consumer attitudes, values and preferences in relation to short food supply chains. These stakeholders have expertise in policy, consumer behaviour, the tourism sector and regulation. The interviewees represented the views of consumers, producers, and other actors who work with or within short food supply in seven European countries (Belgium, Germany, Greece, Hungary, the Netherlands, Spain, and Switzerland). Consumers were generally perceived to be aware of the environmental impact of food production. In terms of preferences, consumers would like to shop for local food the way they shop at the supermarket: having variety of products, accessibility, and availability. The relative lack of convenience and high prices associated with short food supply chains products were seen as the major barriers to their purchase. Consumers were thought to buy the products because of health and environmental benefits, a desire to support their local community, and a preference for tradition. However, relatively few consumers purchase products regularly from SFSC. The main segments are people who believe in short food supply chains values, middle class families with young children and elderly people. More can be done to educate and engage consumers regarding these chains, and market research is needed to inform which strategy is likely to be most effective in specific contexts such as the regional level.